EFEKTIVITAS METODE CARD SORT DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK TENTANG ATHAF DAN MA’THUF - Khalid, Lukman (IAIN Bone, 2020)
This article discusses the effectiveness of the Card Short Method in improving students 'understanding of Athaf and Ma'thuf which aims to determine: (1) The application of the card short method can improve students' understanding of athaf and ma'thuf; (2) The effectiveness of the card short method can improve students' understanding of athaf and ma'thuf. This research is a type of quasi-experimental research design with a nonequivalent control group design. The sample of the experimental class was 25 people and the control class was 25 people. The instruments used in this study were comprehension tests and observation sheets. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive analysis, it was found that the average score of understanding in the experimental class taught by the card sort learning model was 89.37. 86.33 and the mean score of understanding from the control class was 86.33. Meanwhile, based on inferential analysis, the sig value is obtained. amounting to 0,000 which is smaller than 0.05 (0.00 <0.05), thus it can be concluded that h1 is accepted, meaning that there is an effect of card short learning on students' understandings about athaf and ma'thuf material at Madrasah Aliyah Yaminas Nauling Regency Luwu.